Calibration Transfer Chemometrics, Part II: A Review of the Subject - Workman, Jerome; Mark, Howard (Spectroscopy (Springfield, Or.), 2018)
We continue with our review of the methods and mathematics involved with the subject of calibration transfer. Calibration transfer involves several strategies and mathematical techniques for applying a single calibration database consisting of samples, reference data, and calibration equations to two or more instruments. In this installment, we continue by providing a review of the chemometric and tactical strategies used for the calibration transfer process.